(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Information technology is currentlytaking center stage and transformed the whole world into a global village witha global economy, which is increasingly dependant on the creative managementand distribution of information. The enormous advantages it has in easing thedelivery of information around the world. The paper discusses the impact ofinformation technology and role of libraries in the age of knowledge andinformation societies. It also highlights the problems faced by the Library& Information Service (LIS) sector in India and achievements over the yearsusing modern information technologies.